Digital Payment and Online Promotion Effects on Buying Decisions in Digital Retail - Frihatini, Farida; Vernia, Dellia Mila; Haryadi, Rahmat; Hutasuhut, Alya Febryana; Maharani, Iralita (Universitas Airlangga, 2026)
The rapid development of information technology has changed consumer shopping behavior, with conventional transactions becoming part of a more dynamic digital retail ecosystem, as shown by the increase in the use of digital payment systems and online promotion strategies that also influence the way consumers make purchasing decisions. This study aims to analyze the influence of digital payment systems with online promotions on purchasing decisions in the context of modern retail. The research method used is a quantitative method in which primary data is collected from active users of online shopping platforms using structured questionnaires. After that, the data was analyzed using multiple linear regression, which was used to find out the relationship between the variables studied. The results of the study indicate that the digital payment system has had a significant influence on purchasing decisions because it can increase convenience, speed in transactions, and a sense of security for consumers. In addition, online promotion has an important role in shaping consumer preferences in increasing product attractiveness, visibility, and perceived value by consumers. The combination of the two factors indicates that the practical integration of payment systems with promotional strategies can effectively strengthen consumer interest and purchasing decisions. Therefore, retailers need to develop features in digital payments that are safe, efficient, and easy to use. In addition, promotions also need to be designed to be more personal and attractive so that they can increase competitiveness and maintain customer involvement in a competitive digital market.